Photoinvertible Chiral Liquid Crystal that Affords Helicity‐Controlled Aromatic Conjugated Polymers. Issue 20 (31st August 2020) - Yoshida, Satoru; Morikawa, Santa; Ueda, Kenta; Hidaka, Masatomo; Kaneko, Kosuke; Kaneko, Kimiyoshi; Hanasaki, Tomonori; Akagi, Kazuo
Abstract: Photoinvertible chiral compounds are synthesized by linking a photoresponsive bisbenzothienylethene moiety with an axially chiral binaphthyl moiety and used as chiral dopants to prepare a photoinvertible chiral nematic liquid crystal (N*‐LC) field. Subsequently, electrochemical polymerizations of ethylenedioxythiophene (EDOT) in the N*‐LC field to synthesize helical poly(ethylenedioxythiophene)s (H‐PEDOTs) are achieved. The H‐PEDOTs show not only spiral morphologies resembling the fingerprinted texture of N*‐LC in polarizing optical microscope but also bisignate Cotton effects in circular dichroism spectra, indicating the formation of a helically π‐stacked structure in terms of the main chains of H‐PEDOT. In addition, the signs of the bisignate Cotton effect are strictly determined by the helicity of the N*‐LC. The present N*‐LC is the first reaction field exhibiting photoinvertible chirality with extremely high fatigue resistance and serves as an asymmetric medium for electrochemical polymerization, leading to dynamic helicity control of conjugated polymers. Abstract : Novel photoinvertible chiral compounds exhibiting not only remarkably strong fatigue resistance but also large helical twisting powers are synthesized and used as chiral dopants to prepare photoinvertible chiral nematic liquid crystals (N*‐LCs). The electrochemical polymerizations using the N*‐LC as an asymmetric reaction medium produce the helicity‐controlled poly(3, 4‐ethylenedioxythiophene)s with helically π‐stacked structures.